Liquid biopsies in renal cell carcinoma with focus on epigenome analysis - Cimadamore, Alessia; Santoni, Matteo; Massari, Francesco; Cheng, Liang; Lopez-Beltran, Antonio; Scarpelli, Marina; Montironi, Rodolfo (Annals of Translational Medicine, 2019)
We read with great interest the recent paper published by Jung et al. in Clinical Chemistry entitled “Cell-free SHOX2 DNA methylation in blood as a molecular staging parameter for risk stratification in renal cell carcinoma patients: a prospective observational cohort study” (1).